The effect of Ratio of Noni Juice with Pineapple Juice and amount of Sucrose on the Quality of Instant Noni Powder Beverages - Nenny Meiyanti Sitompul; Zulkifli Lubis; Ismed Suhaidi (Universitas Sumatera Utara, 2014)
This research was conducted to determine the effect of noni juice ratio with pineapple juice and amount of sucrose on the quality of instant noni powder beverages. Research was conducted in November - December 2012 at the Laboratory of Food Technology, Faculty of Agriculture, University of North Sumatra, Medan, using a completely randomized design, with 2 factors, i.e ratio of noni juice with pineapple juice (P): (60%:40%, 65%:35%, 70%:30%, and 75%:25%) and amount of sucrose (S): (30%,40%,50%, and 60%). Yield, moisture, total soluble solid, vitamin C, solubility, organoleptic color, flavor and taste were observed. The results showed that the ratio of noni juice with pineapple juice had highly significant effect on yield, moisture, total soluble solid, vitamin C, organoleptic color, flavor and taste, and had no effect on the solubility. Ratioof noni juice with pineapple juice of (75%: 25%) produced the best noni instant powder and more acceptable. Sucrose of 60% produced the best instant noni powder. Keywords: noni powder instant drink, noni, pineapple, sucrose.